MOF‐Derived Bifunctional Iron Oxide and Iron Phosphide Nanoarchitecture Photoelectrode for Neutral Water Splitting. Issue 19 (13th August 2018) - Shit, Subhash Chandra; Mondal, Indranil; Pendem, Saikiran; Bai, Linyi; Park, Jeong Young; Mondal, John
Abstract: The rational design of effective and inexpensive electrocatalysts for solar‐powered water splitting is under intense focus to overcome barriers during half‐cell reactions. Towards addressing this issue, we designed and sequentially synthesized Fe2 O3 and FeP nanoparticles encapsulated on a carbonaceous matrix nanoarchitecture (Fe2 O3 @C and FeP@C) from an Fe‐based 1, 4‐benzenedicarboxylate framework (Fe‐MIL‐88B) through high‐temperature pyrolysis followed by a solid‐/gas‐phase low‐temperature phosphidation process. These nanoparticles were employed as bifunctional electrocatalysts deposited onto a Si photoelectrode assembly. The changes in morphological and electronic properties of the as‐prepared catalysts were investigated after controlled heat treatment. As‐synthesized Fe2 O3 @C/Si and FeP@C/Si were found to be superior bifunctional photoelectrodes in a neutral aqueous medium under simulated solar irradiation of 100 mW cm −2 . Fe2 O3 @C/Si exhibited high activity for the oxygen evolution reaction (OER), providing a photoanodic current density of 2.5 mA cm −2 at 1.65 V (vs. RHE), which was driven by the type‐II heterojunction model in the Fe2 O3 @C/Si system. In parallel, the FeP@C/Si materials exhibited noticeable hydrogen evolution reaction (HER) activity, generating 10 mA cm −2 cathodic current at −0.07 V (vs. RHE). The varied performance could be attributed to the bulk size dependency of the crystalline Fe2 O3 phase on the conductive sp 2 ‐hybridized carbon framework and an intrinsic synergetic effect in the FeP@C, which originates from electronic interactions between Fe and P with high porosity, and which permits easy diffusion of the electrolyte and efficient electron transfer during hydrogen generation. Abstract : Photoelectrodes for neutral water splitting : Fe‐MIL‐88B as a porous network structure gives rise to Fe2 O3 and FeP, encapsulated under conductive carbon matrix, which acts as a superior photoelectrocatalyst atop a Si surface for neutral water splitting. The Fe2 O3 @C/Si exhibits high activity for the oxygen evolution reaction, providing a photoanodic current density of 2.5 mA cm −2 at 1.65 V (vs. RHE), and the FeP@C/Si materials demonstrated noticeable hydrogen evolution reaction activity, generating 10 mA cm −2 cathodic current at −0.07 V (vs. RHE).